The historiography of American foreign relations since 1941 (Cambridge, New York, 1996)
The book includes state-of the art essays and historiographical surveys dealing with U.S. foreign relations since 1941. Part One offers sweeping overviews of the trends in the field of diplomatic history. Part Two features essays that survey the literature on U.S. relatoons with particular regions of the world or on the foreign policies of presidential administrations
Keywords: united states - foreign relations - 1933-1945 - historiography,united states - foreign relations - 1945-1989 - historiography